Development of Animated Videos Using Diary’s Virtual Reality as a Medium Of Distraction on The Anxiety - Rahmawati, Dinda Aprilia; Fatmasari, Diyah; Santoso, Bedjo (Odonto : Dental Journal, 2023)
Background: Dental anxiety refers to anxiety about dental treatment procedures. Dental anxiety is common among pediatric patients because dental treatment procedures are usually a new experience. Therapy and desperate nonpharmacological techniques, which have already become widely used, can alleviate dental anxiety. Virtual reality is one of the various media considered to distract children during dental and oral treatment. Produce a viable Diary's Virtual Reality (VR) media model and its application effectively lowers the anxiety level of child patients upon deciduous tooth extraction action. Method: Experimental design pretest-posttest method with control group design. There were 64 respondents which were divided into; an intervention group given the treatment of watching Diary’s Virtual Reality video and a control group given the treatment of watching video using mobile phones. To assess the child’s level of anxiety when the deciduous tooth is extracted, an MDAS query was used. The test results data of the model were tested using wilcoxon paired test and a Mann-Whitney paired test. Result: The Expert Validation Test of Dary’s VR media earned an average feasibility score of 97,5% with excellent categories with p-value=0,000. The paired data effectiveness test results showed an intervention group p-value=0,000 and a control group=0,010. The test results of the effectiveness of unpaired variable data show that the p-value between the intervention group and the control group is p=0,000. The Diary’s VR model effectively lowers the anxiety level of child patients. Conclusion: Giving Intervention Diary’s VR lowers the anxiety level of child patients significantly compared to the control group.